2014
DOI: 10.1038/hdy.2014.114
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on genetic effects of artificial and natural habitat fragmentation on Loropetalum chinense (Hamamelidaceae) in Southeast China

Abstract: Elucidating the demographic and landscape features that determine the genetic effects of habitat fragmentation has become fundamental to research in conservation and evolutionary biology. Land-bridge islands provide ideal study areas for investigating the genetic effects of habitat fragmentation at different temporal and spatial scales. In this context, we compared patterns of nuclear microsatellite variation between insular populations of a shrub of evergreen broad-leaved forest, Loropetalum chinense, from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…ZSA is an oceanic island that has undergone long-term isolation of ca. 7000-9000 years 27 . Long-term oceanic isolation decreased the genetic diversity and increased the genetic differentiation of insular populations, while there were small genetic effects on the TIL islands that experienced short-term isolation by water.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ZSA is an oceanic island that has undergone long-term isolation of ca. 7000-9000 years 27 . Long-term oceanic isolation decreased the genetic diversity and increased the genetic differentiation of insular populations, while there were small genetic effects on the TIL islands that experienced short-term isolation by water.…”
Section: Discussionmentioning
confidence: 99%
“…The Zhoushan Archipelago (ZSA), located in the East China Sea, was originally a part of mainland China and formed by rising sea levels ca. 7000-9000 years ago 27 (Fig. 1).…”
Section: Plant Materials and Sampling Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been the focus of long‐term biodiversity monitoring since 2002 for a wide range of taxa, including birds (Ding et al , ; Si et al , ), plants (Hu et al , ; Yu et al , ), spiders (Wu et al , ), reptiles (Wang et al , , ), amphibians (Wang, Lane, & Ding, ) and mammals (Wang et al , ; Xu et al , ). These studies explored the biodiversity distribution patterns, including alpha and beta diversity (Yu et al , ; Si et al , ), in these newly formed islands through a genetic‐, species‐, functional‐ and phylogenetic‐based approach (Yu et al , ; Ding et al , ; Yuan et al , ; Si et al , ), and by considering temporal changes in biodiversity (Hu et al , ; Song et al , ) aim to explore the mechanisms of biodiversity maintenance in these fragmented islands (Wilson et al , ). These studies have shown that biological communities are less diverse, more functionally similar and phylogenetically clustered on small and isolated islands (Ding et al , ; Si et al , ).…”
Section: Impacts Of Forest Fragmentation On Biodiversitymentioning
confidence: 99%
“…They have been the focus of long-term biodiversity monitoring since 2002 for a wide range of taxa, including birds Si et al, 2017), plants (Hu et al, 2011a;Yu et al, 2012), spiders , reptiles (Wang et al, 2010c, amphibians (Wang, Lane, & Ding, 2012) and mammals (Wang et al, 2010c;Xu et al, 2014). These studies explored the biodiversity distribution patterns, including alpha and beta diversity (Yu et al, 2012;Si et al, 2016), in these newly formed islands through a genetic-, species-, functional-and phylogenetic-based approach (Yu et al, 2012;Ding et al, 2013;Yuan et al, 2015;Si et al, 2017), and by considering temporal changes in biodiversity Song et al, 2018) aim to explore the mechanisms ; around Menglun town in Xishuangbanna ; areas suitable for gibbons in tropical Hainan (Zhang et al, 2010a); and the Taibai Mountain Nature Reserve in Shaanxi (Sun et al, 2009a). The proportion of patches in each size category is shown.…”
Section: (1) the Thousand Island Lakementioning
confidence: 99%